The Obligation of a Father in Fulfilling Nafaqah Māḍiyah and Nafaqah Ḥaḍānah for Children Post-Divorce in Relation to Relevant Legal Regulations - Agung Ramadhan Seli; Hazar Kusmayanti; Yani Pujiwati (Al-Risalah, 2025)
Nafaqah Māḍiyah and Nafaqah Ḥaḍānah are obligations of a father towards his children post-divorce, as regulated in the Compilation of Islamic Law (KHI) and Law Number 1 of 1974 on Marriage. This study aims to examine the legal consequences of a father’s failure to fulfill these obligations based on the Bogor Religious Court Decision Number 1147/Pdt.G/2023/PA.Bgr. The research employs a normative juridical approach with a descriptive-analytical method, analyzing primary, secondary, and tertiary legal materials through library research. The findings indicate that the judicial panel provided legal protection by partially granting the plaintiff’s claim, ordering past maintenance of Rp300,000,000 as compensation for the father’s negligence since the divorce on November 14, 2017, and Nafaqah Ḥaḍānah of Rp7,000,000 per child per month with a 10% annual increase until the children reach 21 years of age. However, because the judge did not request additional evidence, such as the defendant's financial records, the amount of Māḍiyah alimony granted was far less than the plaintiff's claim of Rp854,924,200.